Fluconazole-Associated Birth Defects: A Comprehensive Review - Janssen M. Firth; Nicholas Daniel; Peter J. Hughes (University of Minnesota Libraries Publishing, 2014)
Background: The August 2013 publication of a large historical cohort study in the New England Journal of Medicine has reignited interest in the potential teratogenic effects of fluconazole when used in pregnant females. Fluconazole is an effective and commonly-utilized antifungal medication. Thus, maternal and fetal exposure to fluconazole is expected in the general population, and pharmacists are expected to counsel patients regarding any risks to their prescribed treatment. Methods: A literature review of all published literature indexed to PubMed (January 1966 to October 2013) and International Pharmaceutical Abstracts (January 1975 to October 2013) including fluconazole and teratogenic effects and published in the English language was conducted. Results: Fourteen publications were included for analysis including case reports (n=7), cross-sectional research (n=2), and historical cohort studies (n=5). Conclusion: There appears to be little to no fetal risk resulting from a single dose or short duration antifungal therapy with fluconazole. However, prolonged high-dose fluconazole therapy has increased potential to confer teratogenic effects. In those cases, the risks of such therapy should be weighed against potential benefits.   Type: Student Project